PENINGKATAN KESIAPAN ORANGTUA SELAMA PANDEMI COVID-19 MELALUI WORKSHOP STRATEGI PENDAMPINGAN BELAJAR DARING PADA ANAK - Hafnidar Hafnidar; Ikhyanuddin Ikhyanuddin (LP2M STP Mataram, 2021)
The widespread prevalence of the COVID-19 pandemic has an impact on children and parents psychologically. Children lose important social interactions and academic routines due to sudden school closures. Meanwhile without any preparation the daring class begins immediately. For some parents the condition is severe, the large burden of work at home and office work brought home, as well as the lack of skill support using technology devices. The purpose of this daring child learning mentoring strategy workshop is to prepare parents in conducting daring learning assistance to children, both physically and psychologically. This activity was attended by 35 parents. Finally, parents are ready physically and psychologically before accompanying children to study daring, and have relaxation skills as an intervention when experiencing stress and frustration during the mentoring of children learning daring